Analisis Faktor Internal dan Faktor Eksternal Kepatuhan Keselamatan dan Kesehatan Kerja (K3) pada Pekerja Unit Teknik di PT X Kabupaten Magetan - Dhema Erlina Novianti; Diniyah Kholidah; Rizki Mustika Riswari (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
Engineering units are complex activities with diverse jobs such as maintanace, machine operation and machine supervision. These jobs have a high risk of occupational accidents, so they must comply with Occupational Health and Safety (OHS) to reduce the risk of accidents and improve worker welfare. Occupational Health and Safety (OHS) Compliance can be influenced by internal factors and external factors. The purpose of this study was to identify and analyze the factors that cause Occupational Safety and Health (OHS) compliance. This research method uses quantitative research with a cross sectional research design with logistic regression analysis. Based on the output of statistical tests, the significance results of internal factors of age 0.015 <0.05, tenure 0.009 <0.05, knowledge 0.006 <0.05, attitude 0.016 <0.05, motivation 0.028 <0.05, ability 0.003 <0.05 and the significance results of external factors of work environment 0.12 <0.05. Internal factors (age, tenure, knowledge, attitude, motivation, ability) and external factors (work environment) influence and have a positive relationship with Occupational Health and Safety (OHS) compliance.